SUBTITUSI PARSIAL AGREGAT HALUS DENGAN BOTTOM ASH PADA PEMBUATAN BATA SEMEN - Mufti Amir Sultan; Imran Imran; Rofika Sakti (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
The Tidore Islands Municipal Steam Power Plant uses coal as fuel to generate electricity. Handling of coal waste in the Rum PLTU is done by storing it on empty land so that it is not effective because it can be potentially dangerous for the environment and surrounding communities. Therefore, it is important to use coal waste. One of them is in the construction field such as in the manufacture of cement bricks.The purpose of this study is to determine the level of water absorption and compressive strength of cement brick using bottom ash base material. Water absorption testing is carried out when the specimen has been immersed for 28 days. The test object is weighed in the SSD state and then inserted into the oven and left for 24 hours. Then the test object is left idle and then weighed. Testing of compressive strength was carried out when the specimen was 28 days old.The results of the study show that the absorption rate of cement brick is increasing when bottom ash is added.Meanwhile, for compressive strength, the cement brick has decreased